What's hot and what's not – Identifying publication trends in insect ecology. (17th May 2021) - Andrew, Nigel R.; Evans, Maldwyn J.; Svejcar, Lauren; Prendegast, Kit; Mata, Luis; Gibb, Heloise; Stone, Marisa J.; Barton, Philip S.
Abstract: Research disciplines in science have historically developed in silos but are increasingly multidisciplinary. Here, we assessed how the insect ecology literature published in ecological and entomological journals has developed over the last 20 years and which topics have crossed discipline boundaries. We used structural topic modelling to assess research trends from 34 304 articles published in six ecology journals and six entomology journals between 2000 and 2020. We then identified and compared topics that emerged from the entire body of literature, or corpus, with topics that emerged from a subsection of articles that focused only on insects (insect corpus). We found that, within the entire corpus, topics on 'Community ecology', 'Traits, life history & physiology' and 'Ecological methods & theory' became more prevalent over time (hot topics), whereas 'Population modelling', 'Insect development', 'Reproduction & ontogeny' and 'Plant growth' declined in prevalence over the 20 years we surveyed (cold topics). In the insect corpus, we found that hot topics included 'Thermal tolerance' and 'Disease vectors', whereas cold topics included 'Herbivore phenology', 'Insect‐plant interactions' and 'Parasitoids and parasites'. 'Landscape ecology' was a growth topic area for both corpora. Our findings suggest that insect‐related research is a major component of the broader ecological discipline, and there are topics in ecology where insect research aligns with general ecological trends. However, specific topics unique to the insect corpora – such as insect taxonomy – are fundamental to both insect and ecology research. Abstract : We review 34 304 articles to identify how the insect ecology literature published in ecological and entomological journals has developed over the last 20 years and which topics have crossed discipline boundaries. Our findings suggest that insect‐related research is a major component of the broader ecological discipline, and there are topics in ecology where insect research aligns with general ecological trends. However, specific topics unique to the insect corpora – such as insect taxonomy – are fundamental to both insect and ecology research. Spanish: Las disciplinas de investigación en la ciencia históricamente se han desarrollado en silos, pero cada vez se vuelven más multidisciplinarias. En este trabajo evaluamos cómo se ha desarrollado la literatura sobre ecología de insectos publicada en revistas de ecológia y entomología durante los últimos 20 años, y qué temas han cruzado los límites de estas disciplinas. Usamos modelos de temas estructurales para evaluar las tendencias de investigación de 34, 304 artículos publicados en seis revistas de ecología y seis revistas de entomología entre 2000 y 2020. Luego, identificamos y comparamos los temas que surgieron de todo el cuerpo de literatura, o corpus, con temas que surgieron de una subsección de artículos enfocada solo en insectos (corpus de insectos). Encontramos que, dentro de todo el corpus, los temas sobre 'Ecología comunitaria', 'Rasgos ecológicos', 'Historia de vida y fisiología' y 'Teoría y métodos ecológicos' se volvieron más frecuentes con el tiempo (temas "novedosos"); mientras que 'Modelado de poblaciones', 'Desarrollo de insectos', 'Reproducción y Ontogenia' y 'Crecimiento de plantas' disminuyeron en prevalencia durante los 20 años que analizamos (temas "fríos"). En el corpus de insectos, encontramos que los temas novedosos incluían 'Tolerancia térmica' y 'Vectores de enfermedades'; los temas fríos incluyeron 'Fenología de herbívoros', 'Interacciones entre insectos y plantas' y 'Parasitoides y parásitos'. 'Ecología del paisaje' fue un área temática de crecimiento en ambos temas. Nuestros hallazgos sugieren que la investigación relacionada con insectos es un componente importante de la ecología en términos amplios, con temas en los que la investigación de los insectos se alinea con las tendencias ecológicas generales. Sin embargo, temas específicos exclusivos de los corpora de insectos, como la taxonomía de insectos, son fundamentales tanto para la investigación de insectos como para la ecología. Abstract in Portuguese is available with online material Portuguese: As disciplinas de pesquisa em ciências se desenvolveram historicamente em silos, mas estão se tornando cada vez mais multidisciplinares. Aqui, avaliamos como a literatura sobre ecologia de insetos publicada em revistas de ecologia e entomologia se desenvolveu nos últimos 20 anos, assim como quais tópicos ultrapassaram os limites disciplinares. Usamos modelagem de tópicos estruturais para avaliar as tendências de pesquisa de 34 304 artigos publicados em seis revistas de ecologia e seis revistas de entomologia entre 2000 e 2020. Em seguida, identificamos e comparamos os temas que surgiram de todo o corpo da literatura, ou corpus, com tópicos que surgiram de uma subseção de artigos que enfocavam apenas insetos (corpus de insetos). Descobrimos que, em todo o corpus, tópicos sobre 'Ecologia da comunidade', 'Traços funcionais', 'História de vida e fisiologia' e 'Métodos e teoria ecológicos' tornaram‐se mais prevalentes com o tempo (temas actuais ou quentes); enquanto que 'Modelagem de População', 'Desenvolvimento de Insetos', 'Reprodução e Ontogenia' e 'Crescimento de Plantas' diminuíram em prevalência ao longo dos 20 anos que pesquisamos (temas frios). No corpus dos insetos, descobrimos que os temas quentes incluíam 'Tolerância térmica' e 'Vetores de doenças'; os temas frios incluíram 'Fenologia de herbívoros', 'Interações inseto‐planta' e 'Parasitóides e parasitas'. 'Ecologia da paisagem' foi um tema de crescimento para ambos corpora. Nossas descobertas sugerem que a pesquisa relacionada a insetos é um componente importante da disciplina ecológica mais ampla, e há tópicos na ecologia onde a pesquisa de insetos se alinha com as tendências ecológicas gerais. No entanto, tópicos específicos exclusivos para os corpora dos insetos ‐ como a taxonomia dos insetos ‐ são fundamentais para a pesquisa de insetos e ecologia.